PENGARUH VARIASI JENIS BUSI DAN CAMPURAN BAHAN BAKAR OKTAN 90 DENGAN METANOL TERHADAP KINERJA MOTOR 110 CC: THE EFFECT OF VARIATION OF TYPES OF SPARK PLUGS AND MIXTURE OF 90 OCTANE FUEL WITH METHANOL ON 110 CC MOTOR PERFORMANCE - Wijaksono, Aditia Ahmad; Yuniarto, Agus (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2023)
Methanol (CH3OH) is an alcoholic compound that can be used as an alternative fuel. The high oxygen content in methanol allows for complete combustion and is combined with experiments using various types of spark plugs which is expected with a strong spark burning the fuel and air mixture so that the effect on performance increases. The research was carried out using an experimental method, namely by conducting various experiments using different types of spark plugs, namely nickel spark plugs, platinum spark plugs, iridium spark plugs and variations of 90 octane fuel mixtures with methanol ratios of 0%, 5%, 10% on performance with gas emission measurement criteria. throw away. The results of this study indicate that there is an effect of using 90 octane fuel on exhaust emissions, where the use of platinum spark plugs has the lowest CO value at 4500 rpm with a CO emission value of 2.20%, while the lowest HC value is at 4000 rpm of 1.90 ppm using iridium spark plugs